2013
DOI: 10.1021/ja310056y
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Smart G-Quadruplex Ligand

Abstract: An unprecedented strategy to control the quadruplex- vs duplex-DNA selectivity of a ligand is reported. We designed a compound whose structure can rearrange when it interacts with a G-quadruplex, thereby controlling its affinity. Thus, the first "smart G-quadruplex ligand" is reported, since this ligand experiences a structural change in the presence of quadruplexes but not in the presence of duplexes, ensuring a high level of quadruplex selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
81
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 39 publications
1
81
0
Order By: Relevance
“…Indeed, G‐quadruplex formation has been shown to hinder telomerase activity, but in addition it is implicated in the regulation of gene expression and quadruplex structures have thus become a potential target in oncology . A range of small molecules has been shown to strongly bind and stabilise such G‐quadruplex structures, thereby rendering these compounds potential anticancer drugs . Recent findings, such as the fact that parallel quadruplexes can still act as a substrate for telomerase, suggest, however, that indirect telomerase inhibition is not necessarily the dominant contribution in anticancer activity of quadruplex‐binding ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, G‐quadruplex formation has been shown to hinder telomerase activity, but in addition it is implicated in the regulation of gene expression and quadruplex structures have thus become a potential target in oncology . A range of small molecules has been shown to strongly bind and stabilise such G‐quadruplex structures, thereby rendering these compounds potential anticancer drugs . Recent findings, such as the fact that parallel quadruplexes can still act as a substrate for telomerase, suggest, however, that indirect telomerase inhibition is not necessarily the dominant contribution in anticancer activity of quadruplex‐binding ligands.…”
Section: Introductionmentioning
confidence: 99%
“…A ligand was designed as a template-assembled synthetic G-quartet (TASQ), which can form an external G-quartet stacking onto the end of G-quadruplex with its positive appendages hooked by the negative phosphates of G-quadruplex. 20 Furthermore, a pentacationic manganese(III) porphyrin complex was invented to show a binding affinity 4 orders of magnitude higher than that of duplex DNA. 21 In fact, experiments suggested that certain ligands do more than stabilize G-quadruplexes.…”
Section: Introductionmentioning
confidence: 99%
“…This structure has attracted significant attention due to its proposed role in telomere maintenance and consequently its potential as a target for the development of new anticancer therapies 1, 2, 3, 4. Therefore, a large number of small molecules have been developed over the past two decades with the aim of selectively binding and stabilizing G‐quadruplex DNA 5, 6, 7, 8, 9. Although the structures of single G‐quadruplexes containing four repeats of the 5′‐TTAGGG sequence have been studied in detail,10, 11, 12, 13, 14, 15 less is known about the higher‐order structures formed by longer telomeric sequences 16, 17, 18, 19.…”
Section: Introductionmentioning
confidence: 99%
“…Though a large number of small molecules have been previously developed as single G‐quadruplex DNA binders,5, 6, 7, 8, 9 comparatively very few have been studied (or indeed specifically designed) as binders for multimeric G‐quadruplex structures 24, 25, 26, 27, 28, 29, 30, 31, 32. This includes a chiral cyclic helicene proposed to bind in the cleft between two human telomeric G‐quadruplexes linked by a TTA spacer 25.…”
Section: Introductionmentioning
confidence: 99%